2020
DOI: 10.3389/fnins.2020.00519
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Alterations in Placental and Fetal Cerebrocortical Annexin-A4 and Cerebral Cavernous Malformation Protein 3 Are Associated With Reductions in Fetal Cortical VEGF Receptor Binding and Microvascular Density

Abstract: Jegou et al. (2012) have reported prenatal alcohol exposure (PAE)-induced reductions of angiogenesis-related proteins in mouse placenta. These effects were associated with striking alterations in microvascular development in neonatal cerebral cortex. Here, we employed a rat model of moderate PAE to search for additional proteins whose placental and fetal cortical expression is altered by PAE, along with a subsequent examination of fetal cerebral cortical alterations associated with altered protein expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In this sense, ethanol consumption during gestation also reduces placental efficiency due to reductions in angiogenesis-related proteins. 42,43 However, the results suggest that ethanol consumption during gestation did not gravely affect the development of HZ embryo-placenta units. This could be due to the intricate genetics of the placenta, being noted that it is an organ conformed of a fetal part and a maternal part, which are in constant communication.…”
Section: Discussionmentioning
confidence: 75%
“…In this sense, ethanol consumption during gestation also reduces placental efficiency due to reductions in angiogenesis-related proteins. 42,43 However, the results suggest that ethanol consumption during gestation did not gravely affect the development of HZ embryo-placenta units. This could be due to the intricate genetics of the placenta, being noted that it is an organ conformed of a fetal part and a maternal part, which are in constant communication.…”
Section: Discussionmentioning
confidence: 75%
“…A variety of animal studies have shown that moderate PAE results in decreased cortical blood flow (Bake et al, 2012), changes in cerebral arterial reactivity including vasodilatory responses as a result of increased oxidative stress (Cananzi & Mayhan, 2019), and decreased oxygen and glucose metabolism (Gleason et al, 1997; Gleason & Hotchkiss, 1992; Richardson et al, 1987). In a rat model of PAE, Annexin‐A4, a calcium‐dependent membrane phospholipid binding protein expressed primarily in epithelial cells was upregulated in the fetal cerebral cortex, and has been associated with neurotoxicity in several neuropathologies (Savage et al, 2020). In addition, PAE decreased the expression of cerebral cavernous malformation protein 3 (CCM‐3) in the ventricular zone of the cerebral cortex (Savage et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of PAE, Annexin‐A4, a calcium‐dependent membrane phospholipid binding protein expressed primarily in epithelial cells was upregulated in the fetal cerebral cortex, and has been associated with neurotoxicity in several neuropathologies (Savage et al, 2020). In addition, PAE decreased the expression of cerebral cavernous malformation protein 3 (CCM‐3) in the ventricular zone of the cerebral cortex (Savage et al, 2020). In the presence of VEGF, CCM‐3 is recruited to cell membranes where it protects VEGFR2 receptors from endocytosis, promoting angiogenesis during development and promoting migration of pyramidal cells and radial glia (Savage et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations